ABORTUS HABITUALIS PADA ANTIPHOSPHOLIPID SYNDROME - L P. Kalalo; S. Darmadi; E. G. Dachlan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
A 30 year old woman, complaining no menstruation for 5 months and had abortion history about 5 times, was admitted to the Dr.Soetomo Hospital outpatient unit. She was then diagnosed of antiphospholipid syndrome on pregnancy. The diagnosis was erected bythe presence of aborts habitualis as a clinical criterion, and the finding of IgG anticardiolipin antibody in two times examination withinterval 9 weeks as laboratory criteria. The criteria were relevant to The International consensus for APS classification (InternationalWorkshop 1999) as well. The patient had lack of financial support so she was just treated with ASA (acetyl salicylic acid), roborantia,and tocolitic-nifedipin or alilestrenol whenever they are needed. These medications were administered until the baby was delivered bysectio caecarea (healthy and normal baby).